Book Review: Pant, Harsh V. (ed.), 2012. The Rise of China: Implications for India. (June 2014) - Kumar, Sumit
Pant, Harsh V. (ed.), The Rise of China: Implications for India (New Delhi: Cambridge University Press India, 2012). Pp. 270, Price ₹ 795.